2009
DOI: 10.1093/carcin/bgp124
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine genetic polymorphisms and prostate cancer aggressiveness

Abstract: Prostate cancer (PCa) is one of the most common cancers in the world. Inflammation has been described as a risk factor for PCa and depends on the production of cytokines in response to tissue damage or the presence of stimuli that induces cellular stress. Interindividual variation in cytokine production is partially controlled by single-nucleotide polymorphisms (SNPs) that have been associated with differential production of cytokines. We have recently showed that SNP-SNP interactions of cytokine genes are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
0
45
1
Order By: Relevance
“…31 For example, a previous report found that the association of IL-10 SNPs with PCa aggressiveness in CaucasianAmerican individuals and cytokine gene-SNP interactions might have a role in this process. 32 Many tumors induce various productions of cytokines, including IL-6, IL-8, IL-10 and tumor necrosis factor, to promote their own growth and limit immune responses. 33,34 Modulation and interactions of these cytokine productions may be pivotal for the control of inflammation and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…31 For example, a previous report found that the association of IL-10 SNPs with PCa aggressiveness in CaucasianAmerican individuals and cytokine gene-SNP interactions might have a role in this process. 32 Many tumors induce various productions of cytokines, including IL-6, IL-8, IL-10 and tumor necrosis factor, to promote their own growth and limit immune responses. 33,34 Modulation and interactions of these cytokine productions may be pivotal for the control of inflammation and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…One important gene identified by this strategy was IL-8. High levels of IL-8 have been found in various human diseases and malignancies (17)(18)(19)(20)(21). IL-8 levels were found to be highly expressed in saliva of OSCC patients (22).…”
Section: Oral Squamous Cell Carcinoma (Oscc)mentioning
confidence: 99%
“…A role for IL8 in angiogenesis and its potential as a therapeutic target in cancer was demonstrated using fully-humanized antibodies to this protein in a mouse model of melanoma [87] , and it was subsequently shown that IL8 increases expression of the key proangiogenic ligand VEGF in endothelial cells resulting in a self-reinforcing, autocrine loop through the VEGF receptor 2 (VEGFR2) expressed on the surface of these cells [88] . Correspondingly, polymorphisms in the IL8 gene were shown to be associated with more aggressive prostate cancer [89] . CXCL1 is also a proangiogenic cytokine and has a potential role in the development of tumor resistance to anti-VEGF based therapy [90] , and in gastric cancer has been shown to promote tumor growth through the VEGF pathway [91] .…”
Section: Hox Transcription Factors and Angiogenesismentioning
confidence: 98%